Pathogenicity of Nomuraea rileyi (Farlow) samson stored for six years - da Silva, Lucianita; Loch, Luiz Canicio (Pesquisa Agropecuaria Brasileira, 1993)
Dead caterpillars of Anticarsia gemmatalis Hübner (Lep. Noctuidae) covered with spores of Nomuraea rileyi (Farlow) Samson from six counties were maintained in jelly capsules and stored in capped glass containers with silica at the temperature of -18°C from 1984 to 1990. The isolates kept their viability and pathogenicity up to six years of storage.